2014
DOI: 10.1002/jat.3088
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced, synergistic late effects of a single dose of radiation and aging: significance in LKS fraction as compared with mature blood cells

Abstract: The number of murine mature blood cells recovered within 6 weeks after 2-Gy whole-body irradiation at 6 weeks of age, whereas in the case of the undifferentiated hematopoietic stem/progenitor cell (HSC/HPC) compartment [cells in the lineage-negative, c-kit-positive and stem-cell-antigen-1-positive (LKS) fraction], the numerical differences between mice with and without irradiation remained more than a year, but conclusively the cells showed numerical recovery. When mice were exposed to radiation at 6 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…28 In addition, single-dose (2-Gy) whole-body irradiation at 6 weeks or 6 months of age induced further upregulation of cyclin D1 and PiK3r1 in the LKS cells in 21-month-old mice. 2 On the basis of these previous observations, it can be hypothesized that, in the steady-state hematopoiesis in old mice, cells in the LKS population proliferate to compensate for their functional impairments within downstream progenitorial daughters. Simultaneously, it may be considered that ineffective hematopoiesis also progresses without any increase in the number of differentiated HPCs with aging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 In addition, single-dose (2-Gy) whole-body irradiation at 6 weeks or 6 months of age induced further upregulation of cyclin D1 and PiK3r1 in the LKS cells in 21-month-old mice. 2 On the basis of these previous observations, it can be hypothesized that, in the steady-state hematopoiesis in old mice, cells in the LKS population proliferate to compensate for their functional impairments within downstream progenitorial daughters. Simultaneously, it may be considered that ineffective hematopoiesis also progresses without any increase in the number of differentiated HPCs with aging.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, it was reported that beta-catenin, cyclin D1, and PiK3r1 appeared to be downregulated in bone marrow cells of aged mice, 2 suggesting that hematopoiesis in the old group was suppressed in the steady state, specifically that in immature HPCs. In addition, although there was no significant ....................................................................................................................... difference in the cell cycle of CFU-GM or CFU-S9 between the nonirradiated young and old groups, the irradiated young and old groups showed marked differences in the cell-cycle parameters of HPCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, there is a growing amount of preclinical (75, 76) and clinical evidence from the bone marrow transplant field (77, 78), as well as the published finding from radiation accidents such as Tokai-mura (79), that despite the early normalization of circulating cell numbers, measures that solely target recovery of the bone marrow stem cell population numbers fail to restore a fully functional hematopoietic compartment and do not protect against downstream systemic late radiation-induced effects.…”
Section: Countermeasure Efforts: Targets/approaches/alternativesmentioning
confidence: 99%